The health technology assessment system in Australia - V. V. Omelyanovskiy; E. S. Saybel; T. P. Bezdenezhnykh; G. R. Khachatryan (IRBIS LLC, 2020)
In Australia, the federal government is in charge of providing the health care to patients. The government agencies determine the list of reimbursable pharmaceuticals and medical services and also define the preferential categories of the population. The states and territories may have their own health care programs in addition to the federal ones. The Pharmaceutical Benefits Advisory Committee (PBAC) is responsible for the health technology assessment (HTA) and decides which technology is eligible for reimbursement by the federal budget. The drug evaluation process includes five stages: a review of general information about the product, assessment of its clinical efficacy, cost-effectiveness analysis, assessment of financial implications of including the drug in the reimbursement list, and consideration of any other factors that may influence the committee decision. In addition to the full reimbursement of pharmaceuticals, the committee may decide to provide funding based on a managed entry agreement.